Type B insulin resistance syndrome. Issue 4 (August 2016) - Willard, Devina L.; Stevenson, Mary; Steenkamp, Devin
Abstract : Purpose of review: To review the epidemiology, pathophysiology, clinical features, and management of type B insulin resistance syndrome. Recent findings: Type B insulin resistance syndrome is a rare disorder caused by autoantibodies to the insulin receptor. This disorder is most frequently reported in middle-aged black women and is invariably associated with other autoimmune diseases. Typically, refractory transient hyperglycemia and extreme insulin resistance are the cardinal features, but hypoglycemia may also occur. Traditionally, the high reported mortality rate was typically attributed to the hypoglycemia. There is no well standardized treatment regimen. However, recent therapeutic advances with combination immunomodulatory therapy have led to significant reported improvements in hypoglycemia-associated mortality and durability of remission. Summary: We review the literature on the pathophysiology and clinical features of type B insulin resistance syndrome and highlight the complexities and recent advances in the management of this disorder.